Perfil de Selênio e Zinco em gestantes saudáveis - Vianna, Cláudia Michielin Della Colleta [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Objective: To evaluate the profile of total selenium and zinc in eutrophic, overweight and obese women. Methodology: A cross-sectional study was carried out in 126 either gestational period women, being them either eutrophic or obese pregnant women. Biochemical markers were assessed: total zinc and selenium, in addition to anthropometric measurements and food intake. Participants will be divided according to body mass index, the control group (CG) of: 42 eutrophic pregnant participants; group (OG) of: 42 overweight pregnant women; and group (OWG) of: 42 obese pregnant women. Statistical tests for equality between groups, parametric tests and the association between BMI and profile of Se and Zn were performed, considering significant differences the value of p <0.05. Results: There was no significant difference between the three groups regarding the average values of zinc in plasma (CG, 53±7 μg/dl; OWG, 57± 8 µg/dl; OG, 55±6 µg/dl) and selenium plasma (CG, 45±12 µg/L; OWG, 48±12 µg/L, OG, 43±6µ g/L) and there was no significant difference in mean values between the three groups for zinc in the erythrocyte (CG, 11±3 µg/ml; OWG, 10±3 µg/ml; OG, 10±2 µg/ml) and selenium in erythrocytes (CG 64±17µg/L; OWG of 63±17 µg/L; OG 60±13 µg/L). Conclusion: The present study demonstrated the presence of deficiency of the micronutrients zinc and selenium in all groups of pregnant women, with and without overweight and obesity. However, more studies are needed to better understand the consequences of changes in micronutrients in pregnant women and base a possible supplementation.

Objetivo: Verificar o perfil de selênio e zinco total em gestantes eutróficas, com sobrepeso e obesas. Metodologia: Foi realizado um estudo transversal com 126 mulheres entre o segundo e terceiro trimestres gestacional. As participantes, foram classificadas segundo estado nutricional pelo critério de Atalah, como: gestante eutrófica, sobrepeso e obesa. Foram avaliados os marcadores selênio e zinco no plasma e no eritrócito. Foram realizadas medidas antropométricas e avaliação do consumo alimentar. As participantes foram subdivididas segundo o índice de massa corporal, sendo Grupo Controle (GC): 42 participantes gestantes eutróficas; Grupo Sobrepeso (GS): 42 participantes gestantes com sobrepeso; Grupo obeso (GO): 42 participantes gestantes obesas. Foram realizados testes estatísticos para testar a igualdade entre os grupos, testes paramétricos e associação entre estado nutricional e valores de Se e Zn plasmático e eritrocitário, considerando diferenças significativas o valor de p<0,05. Resultados: Não houve diferença significativa entre os três grupos em relação aos valores médios de zinco no plasma (GC, 53±7 mg/dl; GS, 57±8 g/dl; GO, 55±6 g/ dl) e selênio no plasma (GC 45 ± 12 mg/L; GS, 48±12 mg/L; GO, 43±6 μg/L) e não houve diferença significativa nos valores médios entre os três grupos para zinco no eritrócito (GC, 11±3 g/ml; GS, 10±3 mg/ml; OG, 10±2 g/ml) e selênio no eritrócito (GC, 64±17 μg/L; GS de 63±17 mg/L; GO, 60±13 mg/L). Conclusão: O presente estudo demonstrou a presença de deficiência dos micronutrientes zinco e selênio em todos os grupos de gestantes, com e sem excesso de peso. No entanto, mais estudos são necessários para entender melhor as consequências da deficiência de micronutrientes em mulheres grávidas e as bases para uso de uma possível suplementação.
Zinc and selenium profile in healthy pregnant women
Keywords: Selenium; Zinc; Obesity; Pregnancy; Selênio; Zinco; Obesidade; Gestação